FRESHNESS ASSESSMENT OF STORED MEAT BY SPECIFIC ACTIVITY OF GLUTATHIONE TRANSFERASE - Adewale, I.O. (Emirates Journal of Food and Agriculture, 2017)
We described a procedure for the determination of freshness of frozen meat or fish samples during storage periods. Correlations between decline in specific activities of glutathione transferase (GST) in fresh or frozen tissues of cow, chicken and fish with storage time at ambient temperature were examined. When fresh tissue is kept at ambient temperature, or if stored frozen and the sample is defrosted, leading to short or prolonged stay at ambient temperatures (20-30o C), specific activity (?) of GST in the tissue begins to decline gradually with time (?). We report that the relationship between the two parameters is of the form ? = -a? 2 -b? + c; where a, b and c are constants and are dependent on the organ or tissue being examined. This relationship as exemplified by the quadratic equation is valid for all positive values of ? and ? or when either is equal to zero, and permits the extrapolation of one parameter (?, time of storage), if the other one (?, specific activity) is known. The results obtained also permit us to suggest that measurement of residual specific activity of GST in frozen meat or fish samples could provide information about storage history and, by extension, the freshness of the items.